Limitation period of action for specific performance in the sale and purchase of land - Md Dahlan, Nuarrual Hilal (International Islamic University Malaysia, 2004)
Limitation period plays an important part in civil action. Failure to comply with the limitation period would mean that the action instituted could diminish. The limitation period for all actions founded on contract pursuant to section 6 of the Limitation Act 1953 is 6 years. However based on the decided cases, the limitation period for action of specific performance of a contract of sale and purchase of land is 12 years, not 6. This is because all actions for specific performance of contract of sale and purchase of land were held in the decided cases to be actions 'to recover land'. Pursuant to section 9 of the Limitation Act 1953 limitation period for all actions for the recovery of land, is 12 years. However, in the author's view, the limitation period of action for specific performance of contract of sale and purchase of land should, be 6 years instead of 12 years because it is an action founded on contract. This article examines the decided cases which rule that the limitation period must be 12 years and elaborates the grounds to support the contention of the author in this respect. The second part of this article will highlight the importance of defence of limitation, and instead be successfully if the parties plead this defence in their pleading pursuant to section 4 of the Limitation Act 1953. However, this requirement has not been consistently followed by courts. It is in the author's view that the failure of the parties to plead this defence expressly could affect his defence of limitation. This article will attempt to unveil the grounds and policies of the courts concerning the above issues.